#1**0 **

0 = 2x(3/x - 3/2) - 7

2x(3/x - 3/2) - 7 = 0

Solve for x:

2 x (3/x - 3/2) - 7 = 0

2 (3/x - 3/2) x - 7 = -3 x - 1:

-3 x - 1 = 0

Multiply both sides by -1:

3 x + 1 = 0

Subtract 1 from both sides:

3 x = -1

Divide both sides by 3:

**Answer: | x = -1/3**

Guest Jul 3, 2017

#2**0 **

0 = 2x(3/x - 3/2) - 7 distribute the 2x over the terms in the parentheses

0 = 6 - 3x - 7 combine like terms

0 = 13 - 3x add 3x to both sides

3x = 13 divide both sides by 3

x = 13 / 3

CPhill
Jul 3, 2017